2017
DOI: 10.1002/clc.22848
|View full text |Cite
|
Sign up to set email alerts
|

Skin aging parameters: A window to heart block

Abstract: Background Skin acts as a mirror to the internal state of the body. Hypothesis We tried to find the relation between skin aging parameters and the incidence of degenerative AV block. Methods This study included 97 patients divided into 2 groups; group D comprised 49 patients with advanced‐degree AV block, and group C comprised the 48 matched control group. All were subjected to full history taking, thorough clinical examination, calculation of intrinsic skin aging score, and resting 12‐lead surface electrocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…Muscle tissues in the musculoskeletal system are composed of specialised cells called muscle fibres, which contract, thereby generating force. Skeletal muscle tissue is derived from myogenic precursor cells that can differentiate into the skeletal muscle fibres attaching to bone, allowing for movement [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle tissues in the musculoskeletal system are composed of specialised cells called muscle fibres, which contract, thereby generating force. Skeletal muscle tissue is derived from myogenic precursor cells that can differentiate into the skeletal muscle fibres attaching to bone, allowing for movement [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tendons and ligaments are composed of collagen fibres and are important for maintaining joint stability and allowing for controlled movement. Tenocytes, the cells that produce collagen in tendons and ligaments, are elongated fibroblastic cells, derived from MSCs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It evaluates skin aging on the basis of 5 indexes: uneven pigmentation, skin wrinkles, sagging skin, reduced adipose tissues, and benign skin tumors. 2 Seborrheic Keratosis (SK) is the most common benign skin tumor, and it is also one of the conditions that indicate skin aging. In general, SK is also known as basal cell papilloma and is a benign intraepidermal tumor, which is caused by a delay in the maturation of keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Skin health could act as a window to reflect cardiovascular health. It has been shown that skin ageing is associated with degenerative atrioventricular block and facial features are helpful in detecting CAD (Lin et al., 2020; Roshdy et al., 2018). In a multi‐centre cross‐sectional study, Lin et al found that frontparietal baldness, crown top baldness, earlobe crease, preauricular crease, heavy pouch, deep crows‐feet, deep forehead wrinkle, periorbital wrinkle, nasal folds, deep nasolabial sulcus, age spots, oral pale and other facial features were considered to be significantly associated with CAD using a computer deep learning algorithm.…”
Section: Introductionmentioning
confidence: 99%